2008
DOI: 10.1038/mt.2008.61
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vector–mediated SERCA2 Gene Transfer Protects Against Heart Failure and Left Ventricular Remodeling After Myocardial Infarction in Rats

Abstract: Reduced expression of the SERCA2 gene impairs the calcium-handling and contractile functions of the heart. We developed an SERCA2 gene transfer system using lentiviral vectors, and examined the long-term effect of SERCA2 gene transfer in the rat ischemic heart failure model. A lentiviral vector containing the SERCA2 gene was infused into a rat heart by hypothermic intracoronary delivery 2 weeks after myocardial infarction (MI). The transduction efficiency was approximately 40%. Six months after transduction, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 26 publications
0
62
0
Order By: Relevance
“…The SERCA2 gene can be targeted to the myocardium using lentiviral vectors and there is improved cardiac function in a rat model of ischemic cardiomyopathy [25]. This study demonstrated that the therapy prevented geometrical left ventricular remodeling after MI and also improved the survival rate.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The SERCA2 gene can be targeted to the myocardium using lentiviral vectors and there is improved cardiac function in a rat model of ischemic cardiomyopathy [25]. This study demonstrated that the therapy prevented geometrical left ventricular remodeling after MI and also improved the survival rate.…”
Section: Introductionmentioning
confidence: 65%
“…Niwano et al [25] infused a lentiviral vector containing the SERCA2 gene into the rat heart by a hypothermic intracoronary delivery method 2 weeks after myocardial infarction (MI). The SERCA2 gene can be targeted to the myocardium using lentiviral vectors and there is improved cardiac function in a rat model of ischemic cardiomyopathy [25].…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39] For example, LVV-mediated prodynorphin overexpression in mouse stem cells induces a remarkable enhancement of the expression of the two cardiac-promoting genes GATA-4 and Nkx2.5, resulting in a dramatic increase of spontaneous beating activity. 38 In another study, Koyanagi et al 37 provided evidence that Sox2 enhances the pluripotency of circulating mesangioblasts and facilitates their differentiation towards the cardiac lineage; in addition, a significant improvement of cardiac function was observed in vivo after transplantation of the Sox2-transduced cells in mice models of myocardial infarction.…”
Section: Gene Delivery By Lvvs: Induction Of Differentiation and Genementioning
confidence: 99%
“…To give an example, LVV-mediated intra-coronary delivery of SERCA2-which encodes the sarcoplasmic reticulum Ca 2+ -ATPase pump that regulates CMC contraction and relaxation-has been shown to protect against cardiac remodelling and to improve functional parameters of the heart after myocardial infarction, resulting in a better survival rate of the treated mice; the effects observed in vivo are probably the results of molecular remodelling by SERCA2 expression. 39 Similarly, gene therapy can make use of silencing approaches to downregulate the expression of genes leading to a certain disease phenotype: RNA interference technology targeting myotrophin, for example, has been shown to attenuate cardiac hypertrophy in vitro and in vivo through a mechanism involving the inhibition of the NF-kB signalling pathway. 36 Regarding cardiovascular gene therapy, the potential targets are several, such as proteins involved in pathways regulating vascular, muscular and myocardial cell functions.…”
Section: Gene Delivery By Lvvs: Induction Of Differentiation and Genementioning
confidence: 99%
See 1 more Smart Citation